Field synergy analysis of heat transfer characteristics of mixed nanofluid flow in self-excited oscillating heat exchanger tubes - Liu, Xianglong; Wang, Zhaohui; Gao, Quanjie; Sun, Xiao; Yang, Qianwen; Yang, Haonan (Journal of thermal analysis and calorimetry, 2024)
Pulsating heat pipes are widely used in cooling electronic devices, automotive radiators, refrigeration, and air conditioning systems. The addition of nanoparticles is one of the effective ways to improve the heat transfer characteristics of fluids. This paper, based on large eddy simulation (LES) numerical method and field synergy theory, investigates the heat transfer characteristics of Al 2 O 3 /Cu mixed nanofluid in a self-excited oscillating heat exchanger tube. Through multi-objective optimization of field synergy angles, field synergy factors, and structural parameters, the enhanced heat transfer mechanism of mixed nanofluids in a self-excited oscillating heat pipe is investigated. It is found that there is a significant negative correlation between the heat transfer coefficient h at the wall surface of the heat exchanger tube and the synergistic angle β . The incorporation of nanoparticles improves the synergistic properties between the velocity and temperature fields. The optimum structural parameters are L/D = 0.469931, α = 128.9904° and d 2 /d 1 = 2.047937, and the optimization increases Nu by 1.92%, decreases f by 10.46%, and decreases the temperature synergy angle β by 2.24°. At the same time, the orthogonality or lack of orthogonality between isotherms and streamlines determines the extent of synergistic performance in the countercurrent vortex.